PENGEMBANGAN ENSIKLOPEDIA ELEKTRONIK MATERI MAKANANKHAS DAERAH BERBASIS KEARIFAN LOKAL SISWA KELAS 4 SDN GADANG 03 MALANG - Maimana, Maimana; Triwahyudianto; Prihatin Sulistyowati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In the learning process in the fourth grade of SDN Kota Malang, there is a phenomenon in the implementation of learning media. The school has provided adequate digital infrastructure, such as LCD projectors and internet access, but this potential has not been optimized optimally. This study aims to develop learning media in the form of an electronic encyclopedia based on local wisdom that contains information about typical foods from various regions in Indonesia. This development research uses the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were fourth grade students of SDN Kota Malang. The instruments used included a validation questionnaire by material, media, and language experts; teacher and student response questionnaires; and pretest and posttest question sheets to measure the effectiveness of the media. The validation results showed a very high level of feasibility, namely 95% by material experts, 96.6% by media experts, and 94.2% by language experts. The practicality value of the media was 84% from teachers and 92.9% from students. The effectiveness test results showed an increase in scores from an average pretest score of 37.5 to 77 in the posttest, with an N-Gain value of 0.640 in the moderate category. Based on the research results, it can be concluded that the local wisdom-based electronic encyclopedia is effective in improving students' understanding of cultural materials, is appropriate, practical, and effective for use in social studies learning in elementary schools.